Modern strategies for management of glycaemia in type 1 diabetes. (October 2022) - Neupane, Sankalpa; Evans, Mark L.
Abstract: The last decade has seen significant advances in the management of type 1 diabetes mellitus (T1DM). Technology is increasingly prevalent, with increasing numbers of people with T1DM using devices for measuring glucose in real time and/or insulin pumps and connected pen devices for delivering insulin. Increasingly, systems are becoming available that link continuous glucose monitoring to insulin pumps, thus allowing the automation of at least some aspects of insulin delivery. Structured education programmes are of great importance in realizing the potential of the flexible insulin regimens that are now technically possible. These offer individuals with T1DM standardized support and education in counting carbohydrates (and perhaps fat and protein) and in adjusting doses for other behavioural factors. Data from many devices – meters, pumps, continuous glucose monitors and connected 'smart pens'– are downloadable and can be analysed and/or shared with healthcare providers. In this chapter, we describe how modern glucose monitoring and insulin replacement can be used strategically with education to manage glucose concentrations in T1DM.